Same day assessment for adult cochlear implant candidates. (November 2013) - Harris, Frances
Abstract : We describe how our Centre in Cambridge has introduced a same day assessment procedure for profoundly deaf adult cochlear implant candidates. This is an intensive approach to assessment which aims to triage candidates on their first visit. Data for 104 assessments completed during 2011 compares those candidates assessed under the standard protocol and those assessed under the new Same Day Assessment approach. The results for the Same Day Assessment are very encouraging. We have achieved consistency in our clinical decision making, with candidates no more likely to be discharged under the one-day approach than when seen more extensively. Candidates make fewer visits to our centre to complete their assessment. Our timescales are improved, on average reaching a clinical decision quicker than under the extensive assessment approach. Feedback from those candidates assessed intensively has been generally very positive. We have made efficiency savings by using less ENT consultant and nurse time overall.